Critical decisions in hurricane evacuation bridge and roadway closures - Dixon, PhD, Zachary; Drishti, MS, Valecha (Journal of Emergency Management, 2022)
The closure of bridges and roadways during hurricanes can represent an abrupt end to evacuations for the residents of coastal barrier island. Despite the gravity of bridge and roadway closures during hurricane evacuations, their governing policies and practices in the United States are often opaque, poorly defined, or mired in confusion. The lack of clarity among bridge and roadway closure policy rationales and terminology, as well as their wide dissensus, may disrupt public compliance and participation in hurricane evacuations. This article argues for the application of critical decision methods (CDMs) analysis in hurricane evacuation bridge and roadways closures as a means of producing better, evidence-based policies and practices. Using CDM to study the decision-making of the experts responsible for the actual work of closing bridges and roadways in hurricane evacuations can help produce more detailed, evidence-based policies, more compelling communication about those policies, and greater public compliance in hurricane evacuations.